Greening and Water Use Efficiency during a period of high frequency of droughts in the Brazilian semi-arid - Rezende, Luiz Felipe; Alves, Lincoln; Barbosa, Alexandre Augusto; Sales, Aldo Torres; Pedra, George Ulguim; Menezes, Rômulo Simões Cézar; Arcoverde, Gustavo Felipe; Ometto, Jean Pierre (Frontiers in Water, 2023)
A discussion that has occurred in the scientific community is that despite the increase in the frequency of droughts, the semi-arid world may be increasing the density of vegetation due to fertilization by the increase in atmospheric CO2, a phenomenon called "greening". Through this study, we sought to evaluate and discuss whether this "greening" would also be occurring in the Brazilian semiarid and what would be its contribution or counterpoint about droughts. Another topic covered was Water Use Efficiency (WUE), about its contribution to mitigating droughts. We chose eight study areas in which the native vegetation was preserved for periods of around 20 years or more. We used data from the Leaf Area Index (LAI), Gross Primary Productivity (GPP), precipitation, evaporation, transpiration, and soil moisture (SM). We divided into two distinct periods to calculate the means of these variables. We applied the Standardized Precipitation Index (SPI) to identify the frequency of droughts for the period from 1961 to 2020. It was observed that between 2001 and 2020, there was an increase in the relative frequency of extreme and exceptional droughts around 19 and 11%, respectively. Our results showed evidence of "greening" for only two sites that were less impacted by droughts, and it seems that the CO2 fertilizer effect could not compensate for the scarcity of water in the other locations of our study. However, WUE was present in almost all sites, which may be a factor in mitigating the impacts of the high frequency of droughts.